2021
DOI: 10.1186/s12864-021-08048-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression study of miRNAs in the crown tissues of winter wheat grown under natural growth conditions

Abstract: Background Winter wheat requires prolonged exposure to low temperature to initiate flowering (vernalization). Shoot apical meristem of the crown is the site of cold perception, which produces leaf primordia during vegetative growth before developing into floral primordia at the initiation of the reproductive phase. Although many essential genes for winter wheat cold acclimation and floral initiation have been revealed, the importance of microRNA (miRNA) meditated post-transcriptional regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…In rice, miR156 and miR529 are known to target some OsSPL [10,36,93], while the expression profiling of miR156 and miR529 have not been reported in wheat. Only a few studies in wheat have annotated and profiled miRNAs [92,94,95]. In particular, molecular characterization of the miR529 family has not been carried out in wheat.…”
Section: Toward Linking the Functions Between Osspls And Tasplsmentioning
confidence: 99%
“…In rice, miR156 and miR529 are known to target some OsSPL [10,36,93], while the expression profiling of miR156 and miR529 have not been reported in wheat. Only a few studies in wheat have annotated and profiled miRNAs [92,94,95]. In particular, molecular characterization of the miR529 family has not been carried out in wheat.…”
Section: Toward Linking the Functions Between Osspls And Tasplsmentioning
confidence: 99%
“…Degradome confirmed that miR9662a-3ptargeted a mitochondrial transcription termination factor (mTERF). Tae-miR9662a-3p has been reported in wheat under heat stress ( Ravichandran et al., 2019 ) and seedling stages in wheat under drought stress ( Li et al., 2019 ; Wang et al., 2021 ; Yue et al., 2022 ). Tae-miR5200 also showed a significant fold change of 5.47 in HT flag leaf, cleaving the transcript that codes for diacylglycerol kinase, a key enzyme of the lipid signaling pathway that mediates plant growth, development, and responses to biotic and abiotic cues ( Rawat et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are a class of small, single-strand non-coding RNAs that are approximately 21 nucleotides in length ( Rogers and Chen, 2013 ; Yu et al, 2017 ). They exert a negative regulation on the expression of target genes through sequence-based complementarity, resulting in mRNA cleavage or translation repression ( Chen et al, 2015 ; Song et al, 2019 ; Wang M et al, 2021 ). Studies have shown that miRNAs play important roles in plant growth and development, including organ morphogenesis, hormone secretion, and stress response ( Aukerman and Sakai, 2003 ; Sunkar et al, 2012 ; Dong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%